La batalla de Sepea y las Hybristika: culto, mito y ciudadanía en la sociedad argiva - Valdés Guía, Miriam (Gerión. Revista de Historia Antigua, 2005)
The argive defeat at the battle of Sepea against the Spartans meant for Argos the start of a period of changes and of citizen integration, that affected to a part of the dependent population, as well as a time of opening toward more democratic positions. These processes were already related, even in the oldest sources, as Herodotus, with cults (as that of armed Aphrodite) and rites (the Hybristika) of the city in which the assumption of “male” prerogatives (the deliberation and the war) on the part of the women had an essential role. In conclusion, the “democratization” of the city that follows Sepea is introduced in the ideological elaborations of those moments and subsequent ones with “face of woman”.